Distance Varieties Wireless Signals Relations Connected Peer to Peer Computers - Kamaran HamaAliFaraj; Banar Fareed Ibrahim; Azhi A. Salih (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Static website by hypertext markup language (HTML) published over a computer networks with the wireless distances variety are connected by peer-to-peer as a client/server(C/S) based network. The evaluating test started from distanced of (twenty meters, forty meters, sixty meters and up to hundred meters) between both points with the communication media guide-wire and unguided-wireless. In phase-1 (guide-wire evaluation) testing for three different distances between both C/S computers which are (20 meters, 40 meters, 60 meters). Each mentioned distances which tested and record different result. The phase-2 (unguided-wire evaluation) wirelessly for three different distances between both C/S computers which are (20 meters, 40 meters, 60 meters). The network Quality of Service (QoS) in private Network (PRN) or peer to peer (P2P) network is in different distances discovered. The private wired and wireless networks utilized in our proposed system and the performance latency of website will be determinate for the reason of solving traffic/bottleneck problem. The designed constant size of static website-html and installed on Serverside, also connected in different length of (cable UTP or wireless) to several clients in order to test and discover lowest response time. QoS will be finding out in least response time in Network different distance wire and wirelessly with a proper solution in right distance.